Planejamento e desenvolvimento de um serious game voltado ao ensino de saúde bucal em bebês - Morais, Alana Marques de (2011)
Serious games are computer games with serious purposes, such as: training, learning, valuation etc. These games connect the fun of common videogames with features like decision making, assessment systems and educational planning in order to create an engaging learning environment. So these aspects create endless possibilities of use in those games and attract attention from other areas of knowledge. Therefore, the design process becomes increasingly complex and involves multidisciplinary teams. This document presents an interdisciplinary study conducted to define an approach based on communication for the development of a serious game for dentistry, specifically oral health in babies. Thus, in this work presents a stage before the design of the serious games. The focus was to evaluate what is the best approach to be applied to the script of the game in order to define the good way to present the content. In this paper, the term communication approach joins features such as: game play, game design, interaction, narrative, story genre and script. In this project, it was necessary to evaluate which communication approach is appropriate in a serious game aimed at mothers. We developed two prototypes to test different communication approaches. The game's audience, initially the mothers, who are using tests that define the most appropriate for them by offering a poll. After interact with approaches, the mothers answered a form. The data were analyzed through absolute and percentage values. Finally we decided adopt a Playful Approach, because the mothers felt more encouraged to finalize this application compare to Formal Approach. The serious game was developed and a new assessment was conducted to investigate mother s opinions. In this new stage of testing, some changes in behavior were seen in the audience, for example, the increase in the number of mothers who said they had some computer knowledge. However, even when dealing with a more demanding audience, the results remained positive. Data were analyzed descriptively by absolute values and percentages. It was found that 87% of mothers who interacted with the game learned some new knowledge and 53% were able to earn (successfully complete) the game.